2022
DOI: 10.1021/acscatal.2c04806
|View full text |Cite
|
Sign up to set email alerts
|

Combined Computational and Experimental Investigation on the Mechanism of CO2 Hydrogenation to Methanol with Mn-PNP-Pincer Catalysts

Abstract: A theoretical and experimental mechanistic study is presented for the homogeneously catalyzed CO 2 hydrogenation to methanol, using an Mn-PNP-Pincer catalyst in the presence of a Lewis acid cocatalyst and alcohol as a solvent. Quantum chemical computations at the density functional theory and DLPNO-CCSD(T) level of theory suggest the presence of a formate resting state as the most stable intermediate. The concerted activation of dihydrogen via a proton shuttle mechanism and decomposition of a hemiacetal interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
4
7
0
Order By: Relevance
“…The derived molecular structure of 1‐CO 2 (Figure 3) displays the four‐membered {Mn−N−C−O} metallacyclic unit typical for pincer‐type complexes coordinating CO 2 via MLC pathways. This observation is in line with our previous DFT calculations, which predict the formation of this adduct upon reaction of the amido complex 1 with CO 2 [4a] …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The derived molecular structure of 1‐CO 2 (Figure 3) displays the four‐membered {Mn−N−C−O} metallacyclic unit typical for pincer‐type complexes coordinating CO 2 via MLC pathways. This observation is in line with our previous DFT calculations, which predict the formation of this adduct upon reaction of the amido complex 1 with CO 2 [4a] …”
Section: Resultssupporting
confidence: 92%
“…On the other hand, catalytic transformations involving MLC‐type reaction pathways at Mn‐MACHO systems might therefore be substantially slowed down in the presence of CO 2 by formation of stable Mn−(CO 2 ) adducts. This point substantiates an additional rationale to the experimentally observed negative CO 2 reaction order in CO 2 ‐to‐methanol hydrogenation catalysed by 1 [4a] . Along the same line, our findings also corroborate the reported lower reactivity of 1 in hydrogenation of CO 2 to formate salts compared to the N ‐methyl‐substituted analogue [ Mn i PrMe −H ], [4h] as the later cannot form such stable, possibly inhibiting CO 2 adduct.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the metal–ligand cooperation (MLC) mechanism for the CO/CN bond reduction catalyzed by transition-metal complexes, , here, the double active-site mechanism of the CO 2 hydroboration catalyzed by A0 through three catalytic subcycles is proposed in Figure . The possible intermediates and transition states have been investigated, and the predicted relative energies of the stationary points along the reaction pathway are relative to A0 .…”
Section: Resultsmentioning
confidence: 88%
“…This iron-based catalyst with a tripodal scorpionate ligand is very promising for potential industrial applications with a carbon efficiency of 86% and an atom economy of 62%. In 2021, Leitner et al reported a direct HCM process catalyzed by the Mn-PNP pincer complex with a TON of 160 ( p (CO 2 ) = 5 bar, p (H 2 ) = 160 bar, T = 150 °C). , Although progress has been achieved in the HCM, most of the reported catalytic systems either contain low TONs or require rigid reaction conditions. Therefore, the design of efficient homogeneous catalysts with new strategies is highly attractive.…”
Section: Introductionmentioning
confidence: 99%